Projected effects of climate change on marine ecosystems in Southeast Asian seas - Kay, Susan; Avillanosa, Arlene L.; Cheung, Victoria V.; Dao, Hung N.; Gonzales, Benjamin Jareta; Palla, Herminie P.; Praptiwi, Radisti A.; Queirós, Ana M.; Sailley, Sévrine F.; Sumeldan, Joel D. C.; Wan Solahudin, Wan Mohd Syazwan; Then, Amy Yee-Hui; et al. (Frontiers Media, 2023)
The seas of Southeast Asia are home to some of the world’s most diverse ecosystems and resources that support the livelihoods of millions of people. Climate change will bring temperature changes, acidification and other environmental change, with uncertain consequences for human and natural systems, but there has been little regional-scale climate modelling of the marine ecosystem. We present initial dynamically downscaled projections using a biogeochemical model suitable for coastal and shelf seas. A coupled physical-biogeochemical model with a resolution of 0.1° (approximately 11 km) was used to create projections of future environmental conditions under moderate (RCP4.5) and high (RCP8.5) greenhouse gas scenarios. Changes for different parts of the region are presented, including four sensitive coastal sites of key importance for biodiversity and sustainable development: UNESCO Biosphere Reserves at Cu Lao Cham-Hoi An in Vietnam, Palawan in the Philippines and Taka Bonerate-Kepulauan Selayar in Indonesia, and coastal waters of Sabah, Malaysia, which include several marine parks. The projections show a sea that is warming by 1.1 to 2.9°C through the 21st century, with dissolved oxygen decreasing by 5 to 13 mmol m-3 and changes in many other environmental variables. The changes reach all parts of the water column and many places are projected to experience conditions well outside the range seen at the start of the century. The resulting damage to coral reefs and altered species distribution would have consequences for biodiversity, the livelihoods of small-scale fishers and the food security of coastal communities. Further work using a range of global models and regional models with different biogeochemical components is needed to provide confidence levels, and we suggest some ways forward. Projections of this type serve as a key tool for communities and policymakers as they plan how they will adapt to the challenge of climate change.